The mother who cannot provide liberation: family atom analysis of women victims of domestic violence - Guglielmin, Maria Silvia; Testoni, Ines; Pogliani, Ingrid; Prandelli, Marta; Bertoldo, Alice; Verdi, Sibylla (La camera blu. Rivista di studi di genere, 2014)
The present contribution presents the discussion about the analysis carried out on family atoms that were completed in the first psychodrama group meetings carried out in all the Empower Daphne III program partner countries. The issue of the relationship with the mother is central to the aim of the project, in that we hypothesise that the mothers of victims are incapable of educating their daughters about personal autonomy in relation to men, due to the traditional culture in which they grew up in. The article presents information about the use and processing of the survey tool “Family atom ” created by Jacob Moreno and the analysis of the data that emerged in parallel to the reports sent periodically by the psychodramatists to the monitoring and analysis team. From the results three types of maternal relationships emerge (positive, negative and incongruent) that enable us to confirm the initial hypothesis of this action research.